PENELUSURAN PERKEMBANGAN KACAPI SUNDA - Asep Nugraha (Paraguna, 2016)
In the Sundanese  society the  existence of kacapi has passed through a long period of time and space.  This instrument is able to adapt to the social and cultural dynamics ofthe Sundanese society. The instrument has also been well documented by both local and foreign researchers. On one hand, some   kacap i  are  extict   because  they   have   been  left   by  their  main supporters.  On the  other  hand,  some of them   are   remains,  change inshape, and even integrating with other types of art  that emerged at thatcertain  time.   This  phenomenon is   interesting   because   it  shows   theemergence of the various shapes of chordophone  (kacapi) in the Snda region.  This paper describes the assorted shapes of kacapi by tracing  the literatures  about kacapi from old times to today.